2019
DOI: 10.1155/2019/4956016
|View full text |Cite
|
Sign up to set email alerts
|

Diet Alters Serum Metabolomic Profiling in the Mouse Model of Chronic Chagas Cardiomyopathy

Abstract: Chagas disease is caused by Trypanosoma cruzi which is endemic in Latin America. T. cruzi infection results in a latent infection with approximately a third of latently infected patients developing chronic Chagas cardiomyopathy (CCM). CCM is a common cause of cardiomyopathy in endemic regions and has a poor prognosis compared to other cardiomyopathies. The factors responsible for the transition from the asymptomatic indeterminate latent stage of infection to CCM are poorly understood. Our previous studies demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 37 publications
4
22
0
Order By: Relevance
“…T. cruzi infection has been previously found to alter levels of members of the phosphocholine metabolic family in the serum and heart. 30,32,36 Our observation of positive correlation between overall phosphocholines and phosphocholines in mass ranges m/z 400-499, 500-599 vs fibrosis and/or inflammation concurs with our observation of infection-induced elevation in phosphocholines in an independent chronic infection system. 32 Phosphocholines are key factors in metabolism of lipids, choline production, and membrane structure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…T. cruzi infection has been previously found to alter levels of members of the phosphocholine metabolic family in the serum and heart. 30,32,36 Our observation of positive correlation between overall phosphocholines and phosphocholines in mass ranges m/z 400-499, 500-599 vs fibrosis and/or inflammation concurs with our observation of infection-induced elevation in phosphocholines in an independent chronic infection system. 32 Phosphocholines are key factors in metabolism of lipids, choline production, and membrane structure.…”
Section: Discussionsupporting
confidence: 90%
“…We and others previously identified perturbation in acylcarnitine metabolism induced by T. cruzi infection when comparing infected vs uninfected animals. [30][31][32][33]36 In the current study, we found alterations in cardiac tissue acylcarnitine metabolite abundances correlate to severity of cardiac inflammation and fibrosis, as well as serum levels of cardiac fibrosis biomarkers, with mid-chain acylcarnitines in particular negatively correlated with serum PDGF. These results complement previous findings and concur with our prior observation of reduced mid-chain acylcarnitines in the heart of C3H/HeJ mice chronically infected with two different T. cruzi strains, Sylvio X10/4 (DTU TcI) and CL (DTU TcVI).…”
Section: Discussionsupporting
confidence: 52%
“…Prior analysis of hearts from acutely infected mice also showed that cardiac metabolite profiles reflected disease severity, with changes in cardiac acylcarnitines and glycerophosphocholines predictive of acute infection outcome [ 9 ]. Metabolomic analysis of chronic CD has been limited to serum and gastrointestinal tract samples [ 18 , 19 ]. Serum analysis demonstrated significant changes in amino acid and lipid metabolism, particularly acylcarnitines, sphingolipids, and glycerophospholipids [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomic analysis of chronic CD has been limited to serum and gastrointestinal tract samples [ 18 , 19 ]. Serum analysis demonstrated significant changes in amino acid and lipid metabolism, particularly acylcarnitines, sphingolipids, and glycerophospholipids [ 19 ]. Analysis of GI tract samples observed persistent metabolic perturbations in the oesophagus and large intestine in chronic CD, including infection-induced elevation of acylcarnitines, phosphatidylcholines and amino acid derivatives [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…T. cruzi infected mice that are treated with the ER stress inhibitor, 2-Aminopurine or the lipid biosynthesis inhibitor Betulin have a significant modulation in cardiomyopathy, mitochondrial stress, and ER stress during chronic infection [4]. Cardiac lipid levels are regulated by many intrinsic and external factors including genetics, diet, and metabolic status [5]. High-fat diet differentially regulates cardiac parasite load, lipid accumulation, and pathology and survival rate during acute and chronic T. cruzi infection in mice and this effect is dependent on the observed body fat mass [6].…”
Section: Introductionmentioning
confidence: 99%